MOST INTEGRATED VIRTUAL IMAGES OF THE BONES IN THE TEACHING OF HUMAN ANATOMY: ARE THERE ANY DIFFERENCES BETWEEN ONLINE AND ON-SITE TUTOR? - Kazoka, Dzintra; Pilmane, Mara (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Covid-19 situation has seriously disrupted regular traditional methods and tools for Human Anatomy teaching. In order to replace limited access to the real human bones, anatomy educators increased integration and use of virtual images in comparison with the past study processes. The present study was conducted to review 15 Human Anatomy tutors’ responses regarding the most used virtual images of the bones for online teaching from March 2020 to the end of October 2021 vs usual on-site teaching at the Department of Morphology. The interview was designed and feedback was taken from the tutors. The majority of the tutors added to their online practical classes a lot of virtual images from anatomical applications and different available resources, related directly to the isolated bones of the skull. For several tutors the searching, preparation and use of virtual images for online teaching was a novelty with advantages and disadvantages. Some tutors have used the possibilities presented by the pandemic to innovate their teaching of skull bones. Virtual images of the bones are an adequate resource for the early stages of undergraduate teaching, but the learning experience may be further enhanced by providing options for the studies with the use of real specimens.